Genome-Wide Association Study Dissects the Genetic Architecture of Maize Husk Tightness - Jiang, Siqi; Zhang, Haibo; Ni, Pengzun; Yu, Shuai; Dong, Haixiao; Zhang, Ao; Cao, Huiying; Zhang, Lijun; Ruan, Yanye; Cui, Zhenhai (Frontiers in Plant Science, 2020)
The husk is a leafy outer tissue that encloses a maize ear. Previously, we identified the optimum husk structure by measuring the husk length, husk layer number, husk thickness and husk width. Husk tightness (HTI) is a combined trait based on the above four husk measurements. Unveiling the genetic basis of HTI will aid in guiding the genetic improvement of maize for mechanical harvesting and for protecting the ear from pest damage and pathogen infection. Here, we used a maize associate population of 508 inbred lines with tropical, subtropical and temperate backgrounds to analyze the genetic architecture of HTI. Evaluating the phenotypic diversity in three different environments showed that HTI exhibited broad natural variations and a moderate heritability level of 0.41. A diversity analysis indicated that the inbred lines having a temperate background were more loosely related than those having a tropical or subtropical background. HTI showed significant negative correlations with husk thickness and width, which indicates that thicker and wider husks wrapped the ear tighter than thinner and slimmer husks. Combining husk traits with ~1.25 million single nucleotide polymorphisms in a genome-wide association study revealed 27 variants that were significantly associated with HTI above the threshold of P < 7.26 × 10−6. We found 27 candidate genes for HTI that may participate in (1) husk senescence involving lipid peroxidation (GRMZM2G017616) and programmed cell death (GRMZM2G168898 and GRMZM2G035045); (2) husk morphogenesis involving cell division (GRMZM5G869246) and cell wall architecture (GRMZM2G319798); and (3) cell signal transduction involving protein phosphorylation (GRMZM2G149277 and GRMZM2G004207) and the ABSISIC ACID INSENSITIVE3/VIVIPAROUS1 transcription factor (GRMZM2G088427). These results provide useful information for understanding the genetic basis of husk development. Further studies of identified candidate genes will help elucidate the molecular pathways that regulate HTI in maize.